An Assessment Performed on E-Agriculture with Indian Agriculturalists - Yadav, Shivkesh (Journal of Advanced Research in Information Technology, Systems and Management; Vol 4 No 2 (2020): Journal of Advanced Research in Information Technology, Systems & Management, 2021)
Technological importance were an amazing aid for making decisions in numerous fields, specifically in agriculture. The improvement of agriculture has been on below growth for the past few years due to lack of agriculture information and environmental changes. The main purpose of this paper is to attain farmers for his or her cognizance, utilization and perception in e-agriculture. The study used statistical survey layout approach to acquire facts from farmers for his or her awareness in e-trade. The outcomes Received indicated the level of awareness is much less such that there may be a need for e-agriculture for their aid. E- agriculture is platform for helping to advertise of agricultural products. How to cIte thIs artIcle: Yadav S, Yadav S. An Assessment Performed on e-Agriculture with Indian Agriculturalists. J Adv Res Info Tech Sys Mgmt 2020; 4(2): 8-11